Sikap Toleransi Masyarakat Lokal terhadap Masyarakat Transmigrasi Dalam Rangka Mewujudkan Integrasi Nasional - Mariatul Kiptiah; Dian Agus Ruchliyadi; Nurmawadah Nurmawadah (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2021)
Karangan putih village is a village where the village where the villagers have different ethnics. Most of the villagers who live there are transmigrans, although they live in the different culture environment, their implementation about tolerance between each villager are high.This research’s objective is to find aut how the local’s and the transmigrans’ way to interact each other, how the local’s behavior to the transmigrans to create the nasional intergration. This research designed and implemented with the qualitative method. The data collection uses the observation technique and interview. The result of this research data will be analyzed by the data reduction, data display and drawing conclusion. The result of this research shows how the locals interact with the transmigrans at karangan putih village is by mutual assistance form, and to create the mutual respect to the cultural differences, they make a discussion and also to create the national integration, the karangan putih village makes a culture to create the peaceful, safe and sound villagers. Besed on the result of this research, it can be suggested that to build the villagers’ tolerance behavior at karangan putih village to fulfill the best things between the villagers.